LINGUISTIC AND METHODOLOGICAL FOUNDATIONS OF EARLY FOREIGN LANGUAGE LEARNING - Choriyeva Xurmo (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
ABSTRACT: This article explores the linguistic and methodological foundations of teaching foreign languages to young children. The study examines the cognitive, phonetic, and lexical characteristics of early learners, as well as age-appropriate teaching strategies that facilitate language acquisition. Emphasis is placed on interactive methods, play-based learning, and communicative approaches that enhance listening, speaking, and vocabulary skills. The findings provide practical guidance for educators to implement effective and developmentally appropriate foreign language lessons in early childhood education.